Refractory IgG Warm Autoimmune Hemolytic Anemia Treated with Eculizumab: A Novel Application of Anticomplement Therapy - Kim Ma; Stephen Caplan (Case Reports in Hematology)
Warm autoimmune hemolytic anemia (wAIHA) is the most common form of AIHA, with corticosteroids in first-line treatment resulting in a 60–80% response rate. Atypical wAIHA and IgG plus complement mediated disease have a higher treatment failure rate and higher recurrence rate. We report a case of severe wAIHA secondary to Waldenström macroglobulinemia with life threatening intravascular hemolysis refractory to prednisone, rituximab, splenectomy, and plasmapheresis. A four-week treatment of eculizumab in this heavily pretreated patient resulted in a sustained increase in hemoglobin and transfusion independence, suggesting a role for complement inhibition in refractory wAIHA.